Induction Motor Broken Bars Online Detection - Janeiro, Fernando M. (2009)
An on-line diagnosis method for three-phase induction motors using an automatic algorithm based on the analysis of the input current RMS is presented in this paper. This algorithm uses the spectrum of the input current RMS value and allows an interpretation of its magnitude as a severity index. Simulation and experimental results, for both an healthy motor and a motor with broken bars, are presented in order to show the effectiveness of the proposed method.